Tatar Gastronomic Culture Through the Prism of Proverbs and Sayings - Elena L. Iakovleva (Publishing house "Sreda", 2021)
A significant layer in the culture of an ethnic group is folklore, which includes a variety of folk art. It expresses the knowledge and experience of the people. Proverbs and sayings, where the centuries-old wisdom of the ethnic group is conveyed in a concise form, concerning different spheres of life, are of interest for learning. Thanks to proverbs and sayings, it is possible to reconstruct the national picture of the world and its components, but often this aspect remains out of the field of attention of scientists. In this regard, the aim of the study was the proverbs and sayings of the Tatar people concerning food. The hypothesis is put forward that the proverbs and sayings of the Tatar people are able to identify the characteristic features of the gastronomic culture of the Tatars, which includes culinary culture, the culture of eating and gastronomic reflection. The key research methods are analytical and hermeneutical. On their basis, the Tatar proverbs and sayings collected in the 6th volume of the publication «Tatar Folk Art» of the Academy of Sciences of the Republic of Tatarstan edited by H.Sh. Makhmutov are studied. As a result of the analysis, the respectful attitude of the ethnic group to food, the production and preparation of which is associated with hard work, was highlighted. The Tatars reflected their love for certain products and dishes, formulated tips for housewives on farming, paid attention to moderation in food and etiquette in proverbs and sayings. The study confirmed the hypothesis. It is concluded that the acquired knowledge allows us to reconstruct the national picture of the Tatars of the Middle Volga region and the Urals from a new perspective through the prism of proverbs and sayings, to interpret their national culture and many of its components, including everyday life and everyday life.